INFLUENCE OF SOCIAL ECONOMIC FACTORS AND AGRICULTURAL TECHNOLOGY IMPLEMENTATION TOWARD ORANGE CROP PRODUCTIVITY - Dasipah, Euis; Raden Budiasih; Tita Rostikasari (Dinasti Publisher, 2020)
The purpose of this study was to find out and analyze the socio-economic influence of farmers on the level of technological application in orange plantation. The research method used descriptive analysis, while to determine the relationship between variables was done by using a simple non-linear regression test and multiple linear regression test. A survey method was conducted on socio-economic factual description of farmers, the application of agricultural technology, especially orange plantation and its productivity. The unit of analysis is a farmer who was cultivation in 2009 until 2020. The sampling technique was done by two-stage random sampling and obtained a sample of 90 farmers as respondents. The collected data were analyzed analytically descriptive according to the results of hypothesis testing. The result of the research showed that: The application of agricultural technology influenced by socio-economic factors, namely the area of arable land and social media exposure.